RUBBER DAM PLACEMENT: WHY MAJORITY OF SENIOR DENTISTSPRACTICING IN HA’IL, SAUDI ARABIA IGNORES IT? - Asaad Javaid Mirza et al (Baqai Journal of Health Sciences)
Isolation of operating site from saliva and other oral fluids prior to commencing a restorative or endodontic procedure via rubber dam is considered as standard healthcare protocol. Numerous studies have been globally conducted including Saudi Arabia to assess use or non-use of this magnificent method of isolation by dental clinicians. To the best of our knowledge, no such study is available about attitude of dentists working in Ha’il i.e. Northern region of Saudi Arabia. This study has been planned to fill the gap by assessing the dentists’ attitude towards the use of this imperial isolation technique. A meticulously prepared and prepiloted questionnaire was used as survey tool. It was distributed among licensed public sector dentists participating in various continuing dental education programs. The young dentists between 24–35 years of age were found using rubber dam in majority (74%) whereas the 75% senior dentists (age above 35 years) responded as not using rubber dam isolation. The most responded reasons for non-use of rubber dam were difficulty in placement and time consumption